OPTIMIZATION OF PREVENTION OF BULLYING IN MOTHERS IN PREVENTING PHYSICAL VIOLENCE IN ELEMENTARY SCHOOL CHILDREN THROUGH EDUCATION - Siti Mardiyah (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2023)
Bullying is aggressive behavior that is continually or repeatedly used to cause bodily or mental harm to another person or group of people. It can be committed by either individuals or organizations. Mothers' understanding of bullying prevention education can increase so they are more equipped to teach their children how to prevent bullying. The toddler's Posyandu is where the community service will be performed. The activity's results can help mothers understand how crucial it is to stop bullying in kids. On February 15, 2022, the implementation took place, and on March 15, 2022, the monitoring. The teaching techniques included lectures, dialogues, and questions and answers. Informational materials about preventing bullying are utilized as media, and tools. The result of community service activities is that there is an increase in knowledge about bullying from 63.3% to 99,3%.